Function and Gene Network Mapping for Target Genes of miR414 and miR2102 under Drought Stress in Barley (Plant Tissue Culture and Biotechnology, 2026)
Barley (Hordeum vulgare L.), an important crop plant and an annual grain cereal, is widely cultivated in dry areas globally. Barley's drought tolerance is multi-genic. There is little information on the candidate genes linked to drought tolerance.. This study aimed to evaluate the function and gene network mapping for miR414 and miR2102 target genes under drought stress in barley. psRNATargets served were used to find target sequences of desired microRNAs. The results of this study revealed that NUC-L1, At5g14050 (GRF1), YAO, and RPL5A genes exhibited the highest contrast with other genes in the network. The expression of identified target genes was evaluated in two barley genotypes (Nimruz as a drought-tolerant cultivar and Spontaneum as the drought-sensitive species) under drought stress. The expression analysis results showed that each genotype exhibited a distinct expression pattern for the target genes. Nimruz cultivar had a higher expression for all target genes than Spontaneum. The transcription level of NUCL1 increased by about 56-fold under drought stress in Nimruz after 72 hrs, whereas only slight or no significant elevations were observed in Spontaneum. Based on the results, the expression of the GRF1 gene was significantly (P